Southern Lady Code : essays - Ellis, Helen (Doubleday, 2019)
"A fiercely funny collection of essays on marriage and manners, thank you notes and three-ways, ghosts, gunshots, gynecology, and the Calgon-scented, onion-dipped, monogrammed art of living as a Southern Lady" --